Translation and Social Media : In Theory, in Training and in Professional Practice - Desjardins, Renée (Palgrave Studies in Translating and Interpreting, 2017)
This book offers a timely discussion of translation and social media through the lens of three overarching themes that structure the book: theory, training, and professional practice. The author includes references that cite recent translation and social media industry data, while also drawing on contemporary interdisciplinary research to make the content relevant for a wide-ranging audience: students, professionals and researchers alike. Desjardins provides an analysis of some of the new challenges and questions social media pose for translation, which include, but are not limited to, the translation of hashtags and the relevance of indexing, social media literacy and competency in translator training, translator visibility and remuneration in the 'like' economy, tactile modalities in social media branding, and social media monitoring and content translation. Examples from a variety of online social media platforms are provided, including Facebook, Twitter, LinkedIn and Instagram. While written primarily from a Translation Studies' perspective, readers with expertise in Social Media Studies and Communication are also likely to find the content engaging, particularly those interested in intercultural communications and brand management. Renée Desjardins is an Assistant Professor at the University of Saint-Boniface, Canada. Her areas of research include Translation Studies, Canadian Studies, Social Media and Food Studies. She has over ten years of professional translation experience, has worked in social media teams and has taught translation at both the undergraduate and graduate level.- Resumé vydavatel